Beyond the Body:Unravelling the Nexus of XR Dance, Collaborative Practice and Politics - Wandel-Brannigan, Caoimhe (Trinity College Dublin. School of Creative Arts. Discipline of Drama, 2026)
This practice-as-research thesis explores how the integration of immersive technologies alters the conditions of choreographic practice. It attends to three interrelated areas: 1)choreographic methods, 2) the posthuman performing body, and 3) the emergence of new conditions of performance in extended reality (XR), requiring new ethical and collaborative frameworks for these practices. Drawing on dance theory, immersive performance, posthumanism, Greek philosophy, and semiocapitalism, the project develops a conceptual framework for understanding dancing bodies within computer-generated and virtual environments. Simultaneously, it situates XR dance within its cultural contexts, drawing out theoretical and political implications of this integration.Four creative experiments underpin the fusion of theory and practice, each advancing the dialogue between conceptual exploration and choreographic practice. These interdisciplinary, collaborative dance works build upon each other, with each new work adding a layer to the last. Art.i.Fact is a pre-recorded motion capture performance experienced through a virtual reality headset. Traversing Spaces employs a mixed-reality approach, allowing audiences to experience both virtual and physical world simultaneously. The Front uses live motion capture in front of a co-present audience to interrogate liveness, interactivity, and data ethics. A final work, Untitled, conceptualises hybrid, distributed performance as a porous membrane through which digital and physical realities are continuously negotiated. Methodologically, they engage Jo Butterworth's eight-stage choreographic process alongside Lyle Skains' ethnomethodology to capture processual and reflective data. This research generates significant findings across three levels: first, technological structures can prioritise specific movement vocabularies and aesthetic hierarchies, and core spatial and temporal structures are reconfigured through enmeshment with technological logics. Second, the posthuman performing body is both constituted and destabilised through its technological interface, reconceptualised here as a somatic chora. Third, live immersive performance requires new mechanisms for engaging with the persistent data flows it produces. By integrating theoretical inquiry and choreographic experimentation, this study contributes to a critical understanding of XR dance as an emergent performance form. It offers new insights into embodiment, relationality and ethics in technologically mediated choreography and argues for practice-informed ethical frameworks that push beyond the legal imperatives of labour union negotiations in service of equitable and transparent working conditions in the sector.
APPROVED
Keywords: Choreography; Cultural Policy; Digital Dance; Immersive Technology; Motion Capture; Semiocapitalism; Hybrid Performance; Dance Theory; Ethical Framework; Posthumanism; HCI; Dance; Practice-as-Research; Embodiment; Virtual Reality; Augmented Reality; Mixed Reality